Estudo hidráulico de descarga de etanol hidratado carburante a partir de caminhão-tanque - Moraes, Isadora Muller Santos (Universidade Federal de São Carlos, 2024)
Hydraulics is a branch of physics that studies the behavior of liquids, both in motion and at rest, and is responsible for the laws governing fluid transport, with or without hydraulic machines, such as pumps and turbines. Hydrated ethanol, produced from sugarcane and also known as common ethanol, is a liquid fuel widely used as a renewable energy source for fueling motor vehicles. Commonly found at fuel stations, there are several processes involved in getting this product to the final consumer, one of which is transporting the product to a fuel distribution base. This transportation can occur through various modes, including rail, river, pipelines, or by road via tank trucks, which will be the focus of this study. Upon arrival at the distribution base, the tank truck is unloaded by connecting it with hoses to a product discharge line and activating a pump that transfers the product from the tank truck to the storage tank. The unloading time of a tank truck depends on the product characteristics and the discharge line setup, including the distance from the tank truck to the tank, the pump's position and type, the type and diameter of the piping, and the line's equipment (valves, elbows, etc.). The goal of this summarized graduation thesis is to conduct a hydraulic study of the transportation of hydrated ethanol, moving it from a tank truck to the product tank using a pump. The central idea is to analyze aspects of this unloading process, such as pressure loss, pump type, and manometric height, and to suggest improvements that enhance task efficiency and the long-term maintenance of the equipment used. Finally, it is emphasized that hydrated ethanol, produced from sugarcane, is increasingly encouraged for use due to being a green and renewable fuel, serving as an alternative to petroleum derivatives, and thus requiring ever faster distribution to meet its growing volumetric demand.
Hydraulic study of the outflow of hydrated fuel ethanol from a tanker truck
Keywords: Hidráulica; Etanol Hidratado; Combustível; Caminhão tanque; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA